Population biology of Alburnoides Jeitteles 1861 (Actinopterygii: cyprinidae) in Iran - Seifali, Mahvash (2012)
The genus Alburnoides Jeitteles, 1861 is distributed in some geographically isolated basins viz. South Caspian Sea, Namak, Kor, Kavir, Tigris and Orumyieh in Iran. Six species of Alburnoides were reported from the basins of Iran. However, little is known about the morphogeographical variation, genetic divergence, ecological adaptation or biology of this fresh water fish species although it is a widespread taxon in Iran. This is the first report on the genus Alburnoides within the Iranian basins. In this study we investigated the taxonomy, morphometric variation, reproductive biology, feeding habits and population dynamic of the Iranian spirlin during four seasons beginning from July 2008 to June 2009. Morphometric variables analysis of 574 samples from 15 populations of four basins as well as truss network and geometric morphometric study of 802 specimens from 23 populations of five basins in Iran indicated that the populations belonged to three major groups that are shown by the consistency with their morphological features. The first clad include spirlin populations from south of Caspian Sea basin. The second clad comprised the populations found in the Namak and Kor basins and the final clad is the populations from the Kavir and Tigris basins. Details of morphological data indicated that there was a distinct morphological separation of populations of Alburnoides in Iran. The populations from the Namak, Kor, and southern Caspian Sea basins showed a closer morphological relationship than those from the Tigris and Kavir basins. A total of 115 samples of South Caspian spirlin were used for the feeding habit study. Results showed that they specifically consumed greater amount of diatoms (Bacillariophyceae) as their dominant diet. Other diets including detritus, insects and algae also recorded high frequency of occurrence but lower percentage value indicating that they are a generalized diet. Spirlin has short gut structure that generally adopted for the carnivorous style of feeding. There was no significant in changes in feeding diet of spirlin according to sampling period, however monthly variations of diets revealed that spirlin have a higher ability to select more available and diverse preys in summer and lower ability in spring. Results on the sex ratio of 471 specimens of Alburnoides sp population in the South of Caspian Sea basin from north of Iran was found in to be 1: 1.24 (female: male), which is almost close to 1: 1 (females: male). Study on the ovarian maturity of the spirlin revealed the presence of six different maturity stages. Ovaries were also evaluated to calculate the reproductive indices such as GSI, MGSI and DI. High values of the GSI were observed in the month of June and its distinct low value in the month of August indicated that the fish spawn during June–July period. The size at sexual maturity of female spirlin was observed at 56-61 mm. In this study the mean fecundity of the 32 females spirlin used in the study was 1722.92 ( 653.88) eggs per fish. The estimated maximum numbers of ova in females was 3042 and the minimum numbers of ova was 668 which were gathered from specimens ranged 82.18 – 110.47 mm in total length. Studies on age, growth, mortality and population characterization of 1019 specimens of spirlin were conducted for Kesselian stream, south of Caspian Sea. Length frequency data were analyzed by using FiSAT (FAO-ICLARM Stock Assessment Tools) for the estimation of the population parameters. Asymptotic length (L∞), growth coefficient (K) were estimated at 104.48 mm and 1.19/yr. Growth performance index (Ø') was calculated as 4.113. Total mortality (Z) was estimated at 3.40/yr whereas fishing mortality (F) and natural mortality (M) were found to be 2.43/yr and 0.97/yr respectively. The exploitation rate (E) was calculated as 0.71. The present exploitation rate (E = 0.70) indicated that the Caspian spirlin is over exploited in the Kesselian stream.